Macroscopic Effect of Quantum Gravity in General Static Isotropic Gravitational Field (Global Journal of Science Frontier Research, 2024)
In this paper we calculated the self-interaction of the gravitational field and analyzed the effect of the self-interactions in a general static isotropic gravitational field using a semi classical approach We found that the effects of the self-interaction on the gravitational field can be used to explain dark matter